Exploring potentials of antioxidative, anti-inflammatory activities and production of bioactive peptides in lactic fermented camel milk. (December 2021) - Dharmisthaben, Patel; Basaiawmoit, Bethsheba; Sakure, Amar; Das, Sujit; Maurya, Ruchika; Bishnoi, Mahendra; Kondepudi, Kanthi Kiran; Hati, Subrota
Abstract: Camel milk has nutritional and medicinal benefits for the human hosts. The antioxidant activities (ABTS assay, superoxide and hydroxyl free radical assay) in camel milk fermented with Lactobacillus plantarum KGL3A were evaluated. At 48 h (37 °C), the superoxide scavenging activity of free radicals (52.26%), ABTS (62.19%), and hydroxyl scavenging activity of free radicals (61.52%) were measured. The optimal growth conditions for maximal peptide development via proteolytic activity (OPA method) (inoculation rate and incubation time) were determined, and the highest peptide (7.84 mg/ml) was reported at 37 °C for 48 h. Lower molecular weight fermented camel milk peptides decreased the production of proinflammatory cytokines by the lipopolysaccharide treated murine macrophages. Protein profiles had been examined using 2D and SDS-PAGE with a water-soluble extract from fermented camel milk. All 2D spots were trypsin digested and analyzed in RPLC/MS. RP-HPLC was used to analyze 3 kDa and 10 kDa permeates, and RPLC/MS was used to detect peptides. Peakview analysts' tools were used to calculate the raw masses of LC/MS. Most of the new peptides in the Swissport and PIR databases were derived from fermented camel milk protein sequences. Searches in the BIOPEP database confirmed the new antioxidant peptides. Graphical abstract: Image 1 Highlights: Camel milk exhibit bio-functional properties since long. Fermented camel milks contain physiologically Bioactive peptides. Camel milk fermented with Lactobacillus plantarum KGL3A also act as probiotics products with antioxidative and anti-inflammatory activities. Antioxidative peptides were identified from fermented camel milk.